Pirogow’s Amputation: A Modification of the Operation Method - M. Bueschges; T. Muehlberger; K. L. Mauss; J. C. Bruck; C. Ottomann (Advances in Orthopedics)
Introduction. Pirogow’s amputation at the ankle presents a valuable alternative to lower leg amputation for patients with the corresponding indications. Although this method offers the ability to stay mobile without the use of a prosthesis, it is rarely performed. This paper proposes a modification regarding the operation method of the Pirogow amputation. The results of the modified operation method on ten patients were objectified 12 months after the operation using a patient questionnaire (Ankle Score). Material and Methods. We modified the original method by rotating the calcaneus. To fix the calcaneus to the tibia, Kirschner wire and a 3/0 spongiosa tension screw as well as a Fixateur externe were used. Results. 70% of those questioned who were amputated following the modified Pirogow method indicated an excellent or very good result in total points whereas in the control group (original Pirogow’s amputation) only 40% reported excellent or very good result. In addition, the level of pain experienced one year after the completed operation showed different results in favour of the group being operated with the modified way. Furthermore, patients in both groups showed differences in radiological results, postoperative leg length difference, and postoperative mobility. Conclusion. The modified Pirogow amputation presents a valuable alternative to the original amputation method for patients with the corresponding indications. The benefits are found in the significantly reduced pain, difference in reduced radiological complications, the increase in mobility without a prosthesis, and the reduction of postoperative leg length difference.